2023
DOI: 10.1029/2023jg007435
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Deep Carbon Release in an Active Volcanic Field Using Hydrochemistry, δ13CDIC and Δ14CDIC

Abstract: A quantification of the input of deep carbon to the Earth's surface is crucial to understand the carbon budget and carbon biogeochemical processes in active volcanic zone (Caudron et al., 2012;Chiodini et al., 2020;Rivé et al., 2013). It is commonly known that the volcanic eruptions would release a large amount of CO 2 into the atmosphere, which can regulate the climate at the geological timescales (Berner & Caldeira, 1997;Hilton & West, 2020). Recently, it has been recognized that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The basement of the Changbaishan area is Archean‐Proterozoic metamorphic rocks, with shield basalt. There are no evaporite and carbonate outcroppings in this study area (Hahm et al, 2008; Zhong et al, 2023). The volcanic activities of Changbaishan are concentrated in Tianchi volcano.…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…The basement of the Changbaishan area is Archean‐Proterozoic metamorphic rocks, with shield basalt. There are no evaporite and carbonate outcroppings in this study area (Hahm et al, 2008; Zhong et al, 2023). The volcanic activities of Changbaishan are concentrated in Tianchi volcano.…”
Section: Methodssupporting
confidence: 91%
“…The low Δ 14 C DIC values (Figure 4a) observed in the Erdaobai River suggest that DIC was significantly contributed by hydrothermal fluids (Carapezza & Granieri, 2004). We assumed the biogenic DIC had a concentration of 573 μmol L −1 , as reported by Zhong et al (2023), because it closely matched the Δ 14 C value of the atmosphere reported by Hua et al (2021). We considered a Δ 14 C sur value of 0‰ to estimate the isotopic composition of DIC, which represented modern carbon and served as endmember 1 (E1) for our analysis.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations